2017
DOI: 10.1136/bcr-2017-221514
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction due to a jejunal enterolith: an unusual complication of jejunal diverticulitis

Abstract: A 91-year-old woman presented with symptoms of acute bowel obstruction supported by clinical findings. A CT of the abdomen was performed which demonstrated jejunal diverticulosis with a single inflamed, wide necked diverticulum. A large enterolith was found to be impacted in the jejunum just distal to the area of inflammation resulting in small bowel obstruction. The patient underwent emergency laparotomy, which confirmed the CT findings. Small bowel resection was performed. The patient had an uneventful posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…While known complications include acute diverticulitis and SBO secondary to enterolith impaction, cases with both complications concurrently are infrequently reported in the literature. A review of existing literature uncovered only eight reported cases of jejunal diverticulitis with simultaneous enterolith obstruction [ 25 , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], of which three involved bowel perforation ( Table 1.0 ) [ 25 , 27 , 28 ]. To the best of our knowledge, this case is unique in presenting with two sites of perforation and an obstructing enterolith.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While known complications include acute diverticulitis and SBO secondary to enterolith impaction, cases with both complications concurrently are infrequently reported in the literature. A review of existing literature uncovered only eight reported cases of jejunal diverticulitis with simultaneous enterolith obstruction [ 25 , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], of which three involved bowel perforation ( Table 1.0 ) [ 25 , 27 , 28 ]. To the best of our knowledge, this case is unique in presenting with two sites of perforation and an obstructing enterolith.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this case is unique in presenting with two sites of perforation and an obstructing enterolith. All reviewed cases required operative management, with various surgical approaches employed [ 25 , [27] , [28] , [29] , [30] , [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…En pacientes seleccionados con perforación sin obstrucción intestinal ni fistula, algunas series recientes sugieren la posibilidad de abordaje laparoscópico con drenaje y lavado 3 .…”
Section: Discussionunclassified
“…Small stones typically would pass down but large ones may cause obstruction. This is called 'enterolith ileus' and is similar to gallstone ileus (4,(6)(7)(8). This phenomenon has only occasionally been reported in the surgical, gastroenterology or radiology literature, given that many clinicians/ surgeons are still unaware of this condition resulting in delayed diagnosis.…”
Section: Figure 1b Sagittal View Of Computerised Tomography Of Abdome...mentioning
confidence: 99%